Analysis Of The I.T Outsourcing Industry In India - Wen, Cai Yan (2005)
Outsourcing is being increasingly viewed as a strategic management issue rather than just a way to cut costs. This paper analyzes the global and Indian scenarios and what drives companies to outsource and their strategic intent in doing so.It also concentrates on different activities being outsources and explores the reasons for the emergence of India as an outsourcing destination and how it has been able to maintain a comparative advantage over its competing countries.